Disaster Mitigation Using Disaster Education in High Schools in Banyuwangi and Lumajang Regency - Retna Ngesti Sedyati; Suharso, Pudjo; Tiara (Basic and Applied Education Research Journal, 2023)
This article describes the urgency of a disaster education curriculum based on local wisdom as a result of a research study in Banyuwangi and Lumajang Regencies, East Java. These two areas are areas with high disaster risk. Banyuwangi Regency is faced with the risk of a tsunami and Mount Raung eruption, while Lumajang is faced with a flood and Mount Semeru eruption. The research was conducted through surveys, literature studies and qualitative descriptions. Methods of data collection through questionnaires, observation, and literature review. Data analysis uses simple inferential statistics and the Miles Hubberman model. As a result, several high schools in Banyuwangi and Lumajang regencies already have a disaster curriculum. The existing disaster curriculum accommodates local wisdom, as an effort to provide appropriate education to face and manage disasters simultaneously. The developed local wisdom-based curriculum explains the relationship between humans and the natural and cultural environment that surrounds them. The implementation of disaster education is carried out through the integration of disaster education in related subjects and through extracurricular activities. The content of disaster education is a combination of disaster standard materials and local wisdom.